Aus der Arbeit der Bibliothek des ehemaligen Deutschen Entomologischen Institutes. Nachlässe, Konvolute etc. Nachlaß Uhmann, Stollberg. - Marwinski, Felicitas (Contributions to Entomology = Beiträge zur Entomologie, 1981)
Further bundles of papers preserved in the library of the former Deutsches Entomologisches Institut, a collection of papers left to it and a collection of authographs have been put in order.